Study of Phenomenology: the Aggressive Behavior of Soccer Club Supporter - Inne Yellisni Firdaus; Trilia Trilia (GLOBAL HEALTH SCIENCE GROUP, 2020)
Aggressive is a behavior directed to another individual with the intention of hurting or injuring. Aggressive behavior is aimed to others with the assumption that those who do the aggressive actions are not able to feel the pain in others or understand their motives, intentions, and goals which are actually more likely to be outrageous and cause physical and psychological harm, or material loss. This action is intentionally done by someone or institution. The objective was to find the phenomenology of the aggressive behavior of football club supporters in Palembang in 2018. The research method in this study used qualitative study design. A qualitative study is a process of examining understanding by using different methodological traditions in exploring social and human problems. The results obtained from the 7 study themes were as follows: External Influence on Changes of Being Supporter, Environmental Acceptance Response after Being a Football Supporter, Self-Satisfaction as a Supporter Member, Violent Actions Experienced by Football Supporters, and Self-Attitudes Facing Rejection Response. Conclusion: There are various phenomenology of football club supporters in Palembang. Supporters are suggested not to do aggressive actions because they can harm themselves and the surrounding environment. Keywords: phenomenology of supporters aggressive behavior